Hydrogels in Spinal Cord Injury Repair: A Review - Lv, Zhenshan; Dong, Chao; Zhang, Tianjiao; Zhang, Shaokun (Frontiers in Bioengineering and Biotechnology, 2022)
Traffic accidents and falling objects are responsible for most spinal cord injuries (SCIs). SCIs are characterized by high disability and low reversibility and tend to occur among the young, seriously affecting patients’ life and quality of life. The key aims of repairing SCIs are preventing secondary nerve injury, inhibiting glial scarring and inflammatory response, and promoting nerve regeneration. Hydrogels have good biocompatibility and degradability, low immunogenicity, and easy-to-adjust mechanical properties. While providing structural scaffolds for tissues, hydrogels can also be used as slow-release carriers in neural tissue engineering to promote cell proliferation, migration, differentiation, and accelerated repair of damaged tissue. This review discusses the characteristics and advantages of hydrogels as delivery vehicles, expounds on the research progress of hydrogels alone, hydrogels combined with cells and molecules to repair SCI and its prospects in clinical research, and provides new ideas for the treatment of SCI.